Edge-emitting polariton laser and amplifier based on a ZnO waveguide. Issue 1 (December 2018) - Jamadi, O.; Reveret, F.; Disseix, P.; Medard, F.; Leymarie, J.; Moreau, A.; Solnyshkov, D.; Deparis, C.; Leroux, M.; Cambril, E.; Bouchoule, S.; Zuniga-Perez, J.; et al.
Abstract We demonstrate edge-emitting exciton-polariton (polariton) laser operation from 5 to 300 K and polariton amplifiers based on polariton modes within ZnO waveguides. The guided mode dispersion below and above the lasing threshold is directly measured using gratings placed on top of the sample, fully demonstrating the polaritonic nature of the lasing modes. The threshold is found to be smaller than that expected for radiative polaritons in planar ZnO microcavities below 150 K and comparable above. These results open up broad perspectives for guided polaritonics by enabling easier and more straightforward implementation of polariton integrated circuits that exploit fast propagating polaritons, and, possibly, topological protection. Edge-Emitting Polariton lasers: A step closer to two-dimensional all-optical devices A type of laser that can propagate along tiny, two-dimensional horizontal cavities in semiconductor materials at room temperature could be used in novel all-optical devices. Polaritons are quasi-particles created from the resonant coupling of light (photons) and matter (electron-hole pairs, or 'excitons') in tiny enclosed spaces, such as the microcavities fabricated from semiconductor materials. Polariton lasers could enable researchers to build energy-efficient, compact all-optical devices. Guillaume Malpuech at the Institut Pascal in Clermont-Ferrand, France, and co-workers have designed a new type of polariton laser and amplifier operating at room temperature. Their design does not require the use of a microcavity but is based on the use of the polariton guided modes of a ZnO layer. This horizontal, guided geometry is appealing because it is easy to fabricate and to integrate in two-dimensional optical circuits.